Accountability Boost: Internet Reporting and Good Governance in Action: Meningkatkan Akuntabilitas melalui Internet Financial Reporting dan Tata Kelola Perusahaan yang Baik: Analisis Kualitatif - Devy Rahmawati; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2023)
This research examines the implementation of Internet Financial Reporting (IFR) and Good Corporate Governance (GCG) as means to enhance accountability in an organization. Employing qualitative approaches and naturalistic paradigms, this study investigates the application of IFR and the adherence to GCG principles at LAZ Rumah Zakat, a charitable organization. The research employs library research techniques for data collection, analysis, and conclusion drawing. The results reveal a commendable level of internet reporting on the organization's website and a satisfactory implementation of the five principles of GCG at Rumah Zakat. These findings highlight the potential of IFR and GCG in improving accountability and have implications for organizations worldwide seeking to enhance their financial reporting practices and governance mechanisms. Highlights: Implementation of Internet Financial Reporting (IFR): Analyzing the effectiveness of IFR in enhancing accountability. Good Corporate Governance (GCG) Principles: Assessing the adherence to GCG principles and their impact on accountability. Qualitative Analysis: Utilizing a qualitative approach to examine the implementation of IFR and GCG and their implications for LAZ Rumah Zakat. Keywords: Accountability, Internet Financial Reporting, Good Corporate Governance, Qualitative Analysis, LAZ Rumah Zakat.